An Open-source Azure Solution for Scalable Genomics Workflows - Yang-Turner, F; Gripper, L; Swann, J; Do, T; Foster, D; Volk, D; Ramanan, A; Robinson, M; Peto, T; Crook, D (IEEE, 2018)
We present an open-source Azure solution for running scalable genomics workflows. It benefits from state-of-art distributed workflow framework, container and cloud technologies and allows users to create a cluster that is scaled to suit their workload in minutes. We describe the design decisions, solution testing and automation options to support a variety of users for their genomic data analytics. The solution demonstrates a generic and customizable approach to run genomic data analytics workflows on a cloud environment.